Comparison between Ormeloxifene and Norethisterone in reducing menorrhagia in dysfunctional uterine bleeding - Gett, Swati; Singh, Shruti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Dysfunctional Uterine Bleeding (DUB) is a condition that affects nearly every woman at some point in her life. This study aims to compare the efficacy of Ormeloxifene and Norethisterone in reducing menorrhagia in such patients. Methods: This prospective study was done on 100 women presenting with dysfunctional uterine bleeding, of 20-50 years of age, who were ready for follow-up and were allocated into two equal groups, one was given Ormeloxifene and the other was given Norethisterone for a period of 3 months. Haemoglobin levels, endometrial thickness on ultrasound and Pictorial Blood loss Assessment Chart (PBAC) scores were assessed before and after the treatment. Results: It was found that both Ormeloxifene and Norethisterone reduced menorrhagia, with a significant difference in PBAC scores (p value <0.05). There was a notable reduction in PBAC scores in Ormeloxifene group (66.53% change from pretreatment mean value) as compared to Norethisterone group (31.38% change from pretreatment mean value); and same holds true for the change in haemoglobin levels as well as endometrial thickness. Ormeloxifene was found to have a greater effect on heavy menstrual bleeding in comparison to Norethisterone. Conclusions: Ormeloxifene is a new modality and is found to be a better option in reducing menorrhagia in DUB in respect to a greater success rate, better compliance and cost effectiveness.